Short and Efficient Syntheses of Protoberberine Alkaloids using Palladium-Catalyzed Enolate Arylation. - Gatland, A; Pilgrim, B; Procopiou, P; Donohoe, T (Wiley, 2014)
A concise synthesis of the biologically active alkaloid berberine is reported, and a versatile palladium-catalyzed enolate arylation is used to form the isoquinoline core. The overall yield of 50 % is a large improvement over the single, previous synthesis. By design, this modular route allows the rapid synthesis of other members of the protoberberine family (e.g., pseudocoptisine and palmatine) by substitution of the readily available aryl bromide and ketone coupling partners. Moreover, by combining enolate arylation with in situ functionalization, substituents can be rapidly and regioselectively introduced at the alkaloid C13 position, as demonstrated by the total synthesis of dehydrocorydaline. The avoidance of electrophilic aromatic substitution reactions to make the isoquinoline allows direct access to analogues possessing more varied electronic properties, such as the fluorine-containing derivative synthesized here.